Method of modelling the anticipated number of officers leaving the service in maneuver elements of the Interior Troops, Ukraine - Gorodnov, V. P.; Radionov, G. О. (Honor and Law, 2019)
The principle of determining the significant factors affecting the number of discharging officers, and a method of modelling the anticipated number of officers who can discharge by the given time are concerned.